1995
DOI: 10.1002/ajmg.1320560111
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb malformations in DiGeorge syndrome

Abstract: We report on upper limb anomalies in two children with a complete DiGeorge sequence: conotruncal defects, hypocalcemia, thymic aplasia, and facial anomalies. One child had preaxial polydactyly, and the other had club hands with hypoplastic first metacarpal. In both patients, molecular analysis documented a 22q11 deletion. To our knowledge, limb anomalies have rarely been reported in DiGeorge syndrome, and they illustrate the variable clinical expression of chromosome 22q11 deletions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…He did not have cardiac anomalies and serum calcium level was normal. He had polydactyly which was reported previously in DGS [Cormier-Daire et al, 1995].…”
Section: Discussionsupporting
confidence: 51%
“…He did not have cardiac anomalies and serum calcium level was normal. He had polydactyly which was reported previously in DGS [Cormier-Daire et al, 1995].…”
Section: Discussionsupporting
confidence: 51%
“…Cleft palate, thymic hypoplasia, preaxial polydactyly and the holoprosencephalic spectrum have all been described with deletion 22q11.2 [Cormier-Daire et al, 1995]. Features in our case shared with CHARGE syndrome include arhinencephaly, microphthalmia, cleft palate, ear anomalies, and micropenis [Lalani et al, 2006].…”
Section: Discussionmentioning
confidence: 51%
“…The mother had ulnar deviation of the right thumb distal phalanx and her daughter had unilateral postaxial polydactyly. Previously reported foot anomalies include clubfoot and left metatarsus varus [Cormier-Daire et al, 1995]. This report is the first large retrospective study of a series of patients with a 22q11.2 deletion for the presence of skeletal anomalies.…”
Section: Discussionmentioning
confidence: 81%
“…Cormier-Daire et al [1995] reported on 2 patients with a 22q11.2 deletion. One had a right duplicated first phalanx, and the other had bilateral club hands with a hypoplastic left thumb and first metacarpal, and a vestigial right thumb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation